Effectiveness of the Self-Administered Interview and Drawing Pictures for Eliciting Eyewitness Memories. Issue 5 (3rd September 2017) - Matsuo, Kayo; Miura, Hiroshi
Abstract : The Self-Administered Interview (SAI) is a tool that is used to obtain eyewitness memories. Adopting the techniques of the cognitive interview (CI), the SAI was developed in the form of a booklet consisting of several parts. The unique aspect of the SAI is a sketch section that asks eyewitnesses to describe the context of an incident by drawing pictures. This study investigates the effectiveness of the SAI by focusing on the effect of the sketch on memory recall. Participants ( n = 180) watched a crime video and recalled events in a 3 (recall method: SAI, CI, free recall [FR]) × 2 (delay: immediate, one week) between-subjects design. The results showed no significant difference among recall methods when the information from the sketch was excluded. When the sketch information was included, the SAI gained better results than the CI and FR in terms of memory recall. In addition, memory performance was better for the immediate SAI compared with the delayed CI. The practical implications of the SAI are discussed.